Pomegranate flower polysaccharide improves mastitis in mice by regulating intestinal flora and restoring the blood-milk barrier - Li, Jianlong; Yin, Wen; Liang, Yuan; Yang, Zhaoran; Li, Liangliang; Mai, Zhanhai; Yu, Xingjian; Lu, Yabin; Zhang, Zhenping; Abula, Saifuding; Wu, Yi; Wusiman, Adelijiang; et al. (Frontiers in Pharmacology, 2024)
This study explored the inhibitory effect of pomegranate flower polysaccharide (PFPS) on mastitis through in vitro and in vivo models. PFPS is a new type of polysaccharide isolated and extracted from pomegranate flowers. The result revealed that PFPS consists of GalA, Ara, and Gal, and the residues consist of 1,4-GalpA, 1,4-Galp, and 1,3,6-Galp, which contain HG-type and RG-I-type pectin structural domains. In vitro studies showed that PFPS could inhibit LPS-enhanced phagocytosis of RAW 264.7 cells and the release of IL-1β, IL-10, and TNF-α. In vivo, studies showed that PFPS improved xylene-induced mouse ear swelling and carrageenan-induced mouse paw edema by inhibiting inflammatory factors. In the mouse mastitis model, PFPS significantly improved LPS-induced inflammation and oxidative stress in mammary tissue. Intestinal flora sequencing results showed that PFPS could effectively regulate the intestinal flora of mice, reduce the relative abundance of pathogenic bacteria Oscillospira and AF12, and increase the probiotics Blautia, Parabacteroides, Allobaculum, and Clostridiaceae_Clostridium. Therefore ， PFPS ultimately played a role in preventing mastitis by regulating the intestinal flora and further improving the blood-milk barrier. This study provides a scientific basis for PFPS as a potential candidate drug for the treatment of mastitis.